Bullous pemphigoid (BP) patients with selective IgG autoreactivity against BP230: Review of a rare but valuable cohort with impact on the comprehension of the pathogenesis of BP. Issue 2 (February 2022) - Ramcke, Torben; Vicari, Elisabeth; Bolduan, Vanessa; Enk, Alexander; Hadaschik, Eva
Highlights: BP230 + sole reactive bullous pemphigoid (BP) has no autoantibodies against BP180. Clinically, BP230 + BP patients are prone to show a mild disease phenotype. BP mouse models confirm the pathogenic potential of BP230 autoantibodies. Autoantibodies in BP230 + BP are directed against the C-terminal domain of BP230. Abstract: Bullous pemphigoid (BP) is the most common autoimmune blistering disease. BP is characterized by the development of tense blisters induced by tissue-bound specific autoantibodies directed against the major autoantigens bullous pemphigoid autoantigen 180 (BP180, also called BPAG2 or Collagen XVII) and bullous pemphigoid autoantigen 230 (BP230, also called BPAG1 or dystonin). The vast majority of BP patients have autoantibodies targeting BP180, or both, BP180 and BP230. The hemidesmosomal protein BP180 is regarded as the main autoantigen, whereas the pathophysiologic relevance of intracellularly-located BP230 is controversial. A small subpopulation of BP patients selectively reveals autoantibodies against BP230 (BP230 + patients) strongly supporting that BP230 autoantibodies might be sufficient to induce skin pathology. In line, BP animal models have been developed, which successfully mimic a human BP phenotype by targeting BP230. In this context, our group has recently shown that a murine autoantibody targeting BP230 induces subepidermal blisters in vivo. This finding suggests that blister formation in the population of patients with selective autoreactivity against BP230 may share pathophysiologic features of pathogenic anti-BP230 autoantibodies in our murine model. This review summarizes the clinical features of BP patients with selective autoreactivity against BP230, enlightens the currently available BP mouse models targeting BP230 and discusses the potential pathophysiological mechanism of BP230 autoantibodies.